2009
DOI: 10.1111/j.1365-2753.2008.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an at‐home preparation programme for Japanese preschool children: effects on children's and caregivers' anxiety associated with surgery

Abstract: A specially designed at-home preparation programme as an outpatient care is effective to encourage parent-child verbal interaction concerning surgery and reduce both children and caregivers' anxiety associated with surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(112 citation statements)
references
References 20 publications
1
111
0
Order By: Relevance
“…Using the booklet and video to deliver educational intervention is proposed due to the fact that they are relatively easy for administration and have low production cost (Wakimizu et al . ). In addition, video is an effective and efficient teaching tool and a previous study has demonstrated that it is effective in increasing parental knowledge about postoperative pain among children (Greenberg et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using the booklet and video to deliver educational intervention is proposed due to the fact that they are relatively easy for administration and have low production cost (Wakimizu et al . ). In addition, video is an effective and efficient teaching tool and a previous study has demonstrated that it is effective in increasing parental knowledge about postoperative pain among children (Greenberg et al .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, using an educational booklet and video with or without face‐to‐face teaching is a practical and cost‐effective method to prepare parents and their children for surgical hospitalization (Wakimizu et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The pediatric surgery nurses’ role in planning discharge from hospital is quite important (Frisch, Johnson, Timmons, & Weatherford, ; Wakimizu, Kamagata, Kuwabara, & Kamibeppu, ), especially as the time between the operation and the patients’ discharge is very short in outpatient surgery. In this short period, it is the nurses’ responsibility to reduce the patients’ pain, address the anxiety of the patients and families, and inform them about the patients’ home care and possible complications (Browne et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…respond optimally when the information is presented one week before surgery [70]. On the other hand, when time before surgery and the age of children allow this, preparatory materials can be sent directly at home [52]. This method is also accompanied by a high rate of satisfaction of the caregivers involved.…”
Section: Discussionmentioning
confidence: 98%
“…The ADVANCE program has been found to have a positive effect in reducing the incidence of postoperative delirium, shortened discharge time and reduced analgesics use post surgery in comparison with the ordinary use of midazolam or with a simple use of parental presence. One of the Family-centred preparation programs was home-based and was usually run one week before surgery [52]. In this program, parents received a video and an auxiliary workbook to be used at home.…”
Section: Preoperative Preparation Programsmentioning
confidence: 99%